If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = 7 + 2x Solving 5 = 7 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 5 + -2x = 7 + 2x + -2x Combine like terms: 2x + -2x = 0 5 + -2x = 7 + 0 5 + -2x = 7 Add '-5' to each side of the equation. 5 + -5 + -2x = 7 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 7 + -5 -2x = 7 + -5 Combine like terms: 7 + -5 = 2 -2x = 2 Divide each side by '-2'. x = -1 Simplifying x = -1
| 12x+(7-x)2= | | x/3=2/9 | | 2(x+10)=4(x-2) | | -8(4+9x)=3(x-1) | | 25t+30b=750 | | 3x+1=1-3x | | -60+40x=20x | | (t)+2.7=4.5 | | -7(y-2)=-2y+39 | | 6(k-7)-(8+9k)=-4k | | 8n-3(5)= | | x^2+4x=5x | | -2x+21=7x-15 | | 8(2x-4)+5(3x+6)=29 | | (2x+28)(4x+10)= | | -3x+1=-2(3x+10) | | 2w^2+2w=34 | | 5r+15=2.25r | | 3(6+x)=30 | | 3x+4-2-x=14 | | -3(e+4)=4w-5 | | -3+2x=-x-6 | | 1-6x=5-4x | | 22-44= | | 13x+9=-15 | | 2a+4.2=3a-16 | | 2y+4=26 | | XY=98 | | 12p=-4 | | -6n+7n+4= | | 5k+8(k-4)=-84 | | 4x-7=x-34 |